The Development of 4 Mat Instructional Management Model to Promote Nursing of Upper Gastrointestinal Bleeding for Nursing Student - ป้อมจันทร์ ศุภวรรณ; ศรีพิบูลย์บัติ จิราพร (Community and Social Development Journal, 2019)
The objectives of this research are to develop the teaching and learning model 4 MAT and study the effectiveness of 4 MAT instructional management by comparing the academic achievement on nursing of patients with upper gastrointestinal bleeding for nursing students. This research and development consist of 4 steps as follows, 1) analyzing existing teaching practices 2) to develop and verify quality of the instructional model, 3) to implement the instructional model4) to evaluation and improvement. The sample consisted of 5 nursing instructors taught in the nursing course, 1 person with health problems and 2 nd year nursing students at Borommarajonani College of Nursing. Sawanpracharak Nakornsawan, amount 30 people. The instruments used in the study were questionnaires; interview and 4 MAT learning cycles. Data were analyzed by percentage, Average standard deviation and t -test dependent. The result of the research shows that most instructional management problems have lecture methods for students. And the effectiveness, it was found that the samples had scores of nursing achievement in nursing practice for patients. For the Bachelor of Nursing students after studying was higher than before at the significant level of .01.